The girl who dreamt she could fly - Maranan, E.B (Bookmark, Inc., 2007)
"The story of Selina is about a little girl who used to dream at night that she could fly like her friends-the bird, the dragonfly and the butterfly. Growing up, she also had a dream and a wish that her sad world would turn beautiful, happy and peaceful. This story is an adaptation by the author of his original story in Filipino, Ang Batang Nanaginip na Siya'y Nakalilipad, which won 2nd prize in the Carlos Palanca Memorial Awrads for Literature in 2005."